1740 S.C. Acts, An Act for the Better Ordering and Governing of Negroes and other Slaves in this Province, § 41 - (:unkn) unknown (My University, 1740)
And Whereas an ill custom has prevailed in this Province, of firing guns in the night time; for the prevention thereof for the future, be it enacted that if any person shall fire or shoot off any gun or pistol in the night time after dark and before day-light without necessity every such person shall forfeit the sum of 40s. current money for each gun so fired as aforesaid
Keywords: DISCHARGE